2003
DOI: 10.2519/jospt.2003.33.10.615
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Supplementation and Athletic Performance

Abstract: Nutritional supplements and other ergogenic aids have gained widespread use among professional, amateur, recreational, and student athletes for their potential to enhance athletic performance and provide a competitive edge. Creatine monohydrate is one of the more commonly used and potentially beneficial supplements that currently is viewed to be safe. Supplementation with oral creatine augments skeletal muscle creatine concentrations in most individuals, which has been shown to promote gains in lean body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 58 publications
0
7
0
2
Order By: Relevance
“…rapamycin may be attenuated, thereby permitting enhanced anabolic signaling and possibly muscle protein synthesis (Xie et al 2011). An improved resistance to fatiguing exercise is also possible via this mechanism, such as with previous research on creatine monohydrate, which increases ATP availability (Racette 2003), and previous research regarding creatine's capabilities for increasing muscle mass has been well established (Buford et al 2007). However, more thorough research is required before considering this as a viable mechanism because of the fact that previously enhanced intramuscular ATP levels have only been examined in 1 resting subject (Reyes-Izquierdo et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…rapamycin may be attenuated, thereby permitting enhanced anabolic signaling and possibly muscle protein synthesis (Xie et al 2011). An improved resistance to fatiguing exercise is also possible via this mechanism, such as with previous research on creatine monohydrate, which increases ATP availability (Racette 2003), and previous research regarding creatine's capabilities for increasing muscle mass has been well established (Buford et al 2007). However, more thorough research is required before considering this as a viable mechanism because of the fact that previously enhanced intramuscular ATP levels have only been examined in 1 resting subject (Reyes-Izquierdo et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A utilização exógena de creatina se dá por meio da suplementação, normalmente da isoforma monoidratada, nas dosagens recomendadas pelas pesquisas e pareceres internacionais, que variam de 0,3 g a 0,5 g de creatina por quilograma de massa corporal [5][6][7]. Os principais efeitos do consumo exógeno são melhoras ergogênicas e aumento de força muscular, além de potenciais efeitos preventivos a lesões, proteção das células neurais e termorregulação corporal [1][2][3][4][5][6][7][8].…”
Section: Introductionunclassified
“…As discussed by the authors, Muscle Fuel™ contains numerous ingredients and it is, therefore, "impossible to determine which ingredient(s) provided the primary ergogenic response" (Kraemer et al 2007). Nevertheless, we think that the ingestion of creatine and caVeine may have been of major relevance for the improvements in performance in this study, as this has been shown in previous studies (Racette 2003;Rawson and Volek 2003;Volek 2003;Spriet and Gibala 2004). But in our opinion it is of much greater relevance that studies using a polypragmatic approach in nutritional supplementation, which do not allow to analyse the eVects of single substances, are not very helpful for sports medicine and athletes, as physicians, coaches and athletes may be motivated or even forced to supplement many substances simultaneously, and thereby a doping-mentality is generated in athletes.…”
Section: Dear Editormentioning
confidence: 66%